Strategic global repositioning and future economic development in Jamaica - Bernal, Richard L. (North South Centre Coral GablesUS, 1996)
Argues that Jamaica has the potential to become an exporter of services and can thereby achieve economic development. Suggests that for this to be realised, Jamaica must implement policies to achieve strategic global repositioning.